2016
DOI: 10.1016/j.jamda.2015.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Walking-Induced Fatigue Leads to Increased Falls Risk in Older Adults

Abstract: Background For older adults, falls are a serious health problem with over 30% of people over 65 suffering a fall at least once a year. One element often overlooked in the assessment of falls is whether a person’s balance, walking ability and overall falls risk is affected by performing activities of daily living such as walking. Objective This study assessed the immediate impact of incline walking at a moderate pace on falls risk, leg strength, reaction time, gait and balance in 75 healthy adults from 30 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
48
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 46 publications
4
48
1
4
Order By: Relevance
“…The aim of the current study was to examine the patterns of inter-and intraindividual variability of falls risk, leg strength, reaction time and walking ability for both healthy older adults and older persons with T2DM. As expected, the results revealed that increasing age for both groups was reflected by a systematic increase in falls risk and a decline (i.e., slowing) of general motor function in reaction time and walking speed (Dykiert, Der, Starr, & Deary, 2012b;Himann, Cunningham, Rechnitzer, & Paterson, 1988;Morrison et al, 2016;Welford, 1988). Importantly, in addition to this neuromotor slowing, there was increased intraindividual variability for these same measures as a function of increasing age, with the older T2DM individuals being more variable compared to healthy controls.…”
Section: Discussionsupporting
confidence: 71%
“…The aim of the current study was to examine the patterns of inter-and intraindividual variability of falls risk, leg strength, reaction time and walking ability for both healthy older adults and older persons with T2DM. As expected, the results revealed that increasing age for both groups was reflected by a systematic increase in falls risk and a decline (i.e., slowing) of general motor function in reaction time and walking speed (Dykiert, Der, Starr, & Deary, 2012b;Himann, Cunningham, Rechnitzer, & Paterson, 1988;Morrison et al, 2016;Welford, 1988). Importantly, in addition to this neuromotor slowing, there was increased intraindividual variability for these same measures as a function of increasing age, with the older T2DM individuals being more variable compared to healthy controls.…”
Section: Discussionsupporting
confidence: 71%
“…Older persons are more susceptible to muscle fatigue due to decreased muscle strength and sarcopenia. It has been shown that 28 fatigue leads to greater postural oscillation, decreased obstacle negotiation ability, and an increased risk of falling among older persons. Furthermore, some authors have suggested that fatigue should no longer be considered a physical event but rather a sensation or emotion resulting from the interaction between the above aspects and cognitive factors 29,30 explained by the central governor model 31 , in which the regulation of the activity of motor neurons that innervate skeletal muscle fibers to maintain homeostasis by central nervous system is predominantly emotional.…”
Section: Discussionmentioning
confidence: 99%
“…In one mechanistic study, participants walked on an inclined treadmill, and after fatiguing, older participants exhibited increased sway, slower reaction time, decreased lower leg strength, and increased fall risk. 26 Participants who reported that, overall, their health was fair or poor were 86% more likely to fall (aOR 1. survey item is nonspecific, asking "In general, would you say your health is: excellent/very good/good/fair/poor?" Respondents may have been taking into account comorbidities or functional status, both of which have been associated with falls in prior studies.…”
Section: Discussionmentioning
confidence: 99%